2010
DOI: 10.1128/cvi.00223-10
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Pandemic H1N1 2009 Influenza Virus Recombinant Hemagglutinin Protein-Based Enzyme-Linked Immunosorbent Assay for Serosurveillance

Abstract: An enzyme-linked immunosorbent assay (ELISA) for the detection of IgG antibodies against the pandemic H1N1 2009 influenza A virus, employing a recombinant hemagglutinin protein of the virus, was compared to the hemagglutination inhibition (HI) test using 783 serum samples. The results showed a concordance of 98.4%, suggesting the utility of the ELISA in serosurveillance. Two hundred sixty-nine (100%) serum samples with an HI titer of >20 were ELISA reactive.Influenza viruses are negative-strand RNA viruses tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Our study shows that influenza‐specific IgG and IgM antibodies can be measured by ELISA, which has advantages over the HI method. Commercially available IgG and IgM anti‐influenza type A or B ELISAs have been used in literature, but not compared to HI . Another study reported on the use of an IgG ELISA using the pandemic H1N1 HA protein as a coating antigen, and they found a concordance of 98·4% with HI .…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that influenza‐specific IgG and IgM antibodies can be measured by ELISA, which has advantages over the HI method. Commercially available IgG and IgM anti‐influenza type A or B ELISAs have been used in literature, but not compared to HI . Another study reported on the use of an IgG ELISA using the pandemic H1N1 HA protein as a coating antigen, and they found a concordance of 98·4% with HI .…”
Section: Discussionmentioning
confidence: 99%
“…However, this testing cannot differentiate different lineages of the same subtype of the influenza A virus. The majority of individuals have already been exposed to the seasonal influenza A virus, which has almost identical NP and matrix protein sequences; therefore, a 4-fold rise in the complement fixation antibody titer with these antigens indicates a recent influenza A virus infection without differentiating between seasonal H1N1 or H3N2 infection and the pandemic 2009 H1N1 infection (14). Although recombinant H has been found to be sensitive and specific for antibody detection by EIA, cross-reactivity between seasonal H1N1 and pandemic H1N1 may still occur, because their overall amino acid identity was 80.1% for H (440 out of 549 amino acids), 72% for HA1, and 92% for HA2 ( Fig.…”
Section: Antibody Testingmentioning
confidence: 99%
“…When highly pathogenic or novel influenza strains are involved, specialized laboratories with stronger containment facilities and specially trained personnel are required for safe implementation of virus culture and testing . In contrast, ELISA is a suitable alternative for seroepidemiological surveillance testing because it is highly sensitive and easy to perform , . In this study, we describe the development and use of an indirect ELISA method that is based on the use of recombinant HA1 proteins of the 2009 H1N1 viruses isolated from humans in Mexico and from swine in Canada and that specifically recognizes A(H1N1)pdm09 virus antibodies in human serum samples.…”
Section: Serologic Cross‐reactivity Between Pandemic 2009 H1n1 and Sementioning
confidence: 99%